A Mixed-Method Study on Student’s Self-Esteem Skills - Aktepe, Vedat; Bulut, Aydın (Participatory Educational Research (Per), 2024)
This study thereby aimed to determine the students' self-esteem skills and examine them within the framework of different variables. The study was executed with a mixed methods design where quantitative and qualitative research models were used together. Survey Analysis was used for the purpose of quantitative analysis of the study, the sample was determined using the simple random sampling and 330 students participated in the survey population. Data were collected using the “Self-Esteem Questionnaire” as a data collection tool. The data were further analyzed with the SPSS statistical program; the percentage and mean values of the research data were examined, and independent t-test and one-way analysis of variance ANOVA were used to reveal the relation between different variables. Case Study was then used for the purpose of qualitative analysis of the study, the study group was determined with the convenience sampling method of the purposive sampling methods and 29 students participated in the interview. A semi-structured questionnaire was used as a data collection tool and the data were analyzed through content analysis. In accordance with the results of the research, it was concluded that the overall self-esteem level of the students was high, the self-esteem levels were higher in favor of female students however the self-esteem levels of the students did not differ based on the educational background and occupation of their parents. Furthermore, students explained the concept of self-esteem as self-respect, personal care, being organized, self-confidence and establishing good relationships with people.
Keywords: Specialist Studies in Education (Other); self-esteem; skills; student; primary school; mixed-methods study.; Eğitim Üzerine Çalışmalar (Diğer)